Effects of etching process and annealing temperature on the ferroelectric properties of atomic layer deposited Al-doped HfO2 thin film. (15th October 2022) - Ku, Boncheol; Ma, Yue; Han, Hoonhee; Xuan, Wang; Choi, Changhwan
Abstract: An investigation was conducted with regard to the effect of etching process on the ferroelectric (FE) characteristics of different device structures with Al-doped HfO2 thin films; further, the effect of the rapid thermal annealing temperature on the FE properties was elucidated using metal-ferroelectric-metal (MFM) capacitors using TiN electrodes with varying thickness and 4 at.% Al-doped HfO2 FE layer. The capacitors were annealed at different temperatures after lithography and etching process; this was aimed at incorporating the FE-orthorhombic phase. The samples annealed after patterning were able to obtain improved FE characteristics due to the amount of tensile stress. The MFM devices that were initially patterned were also studied as a reference. We found that even though it required higher temperature and shorter time to introduce the FE phase, it exhibited more stable as well as promising FE properties and electrical performances with a relatively large remnant polarization (2 P r ∼ 60 μ C cm −2 ), a coercive electric field of approximately 2 MV cm −1 and high switching current density with less leakage. Our results indicate how the FE properties of the HfO2 -based thin films can be engineered through suitable process sequence and post-annealing conditions, thereby verifying the applicable flexibility of FE-HfO2 for semiconductor device integration.